PENERAPAN PRINSIP NATURE IN THE SPACE DAN NATURE OF THE SPACE PADA HEALTHY PLAZA AVENUE DI KOTA BARU PARAHYANGAN - Rizal Pardamean Sihite; Nurtati Soewarno (JMARS: Jurnal Mosaik Arsitektur, 2021)
Humans are essential can not be separated from nature because humans rely heavily on nature for their survival. Currently including natural elements in the design of a building has become a lifestyle and trend, as seen in some commercial buildings, such as Hotels, Shopping Malls that take the theme of nature. Healthy Plaza Avenue is a planned shopping center to fulfill facilities in Kota Baru Parahyangan, a new residential neighborhood that has a vision of an independent green city. Healthy Plaza Avenue design method starts from problem formulation, data collection, design process, and design products. Nature in the space and Nature of the space are two of the three categories of biophilic design principles that are considered to be appropriately applied to the design of Healthy Plaza Avenue. The application of the principles of Nature in the space and nature of the space is seen in the Atrium by placing ornamental plants and shade trees equipped with waterways that boil in the Event Plaza. While in the outside area is a planned Rain Garden that serves in addition to adding beauty also as a catchment and recycling area for the needs of the building. In addition, hanging plants are also placed on the façade of the building to reflect the green elements so that Healthy Plaza Avenue can be harmonious with the environment. It is hoped that the concept of Nature in the Space and Nature of the Space can be in line with the vision of Kota Baru Parahyangan as an independent city that maintains its environmental beauty.